PEMBELAJARAN PEMANFAATAN DATA SIFAT HUJAN DAN PRANATA MANGSA BAGI PETANI UNTUK MENENTUKAN MASA TANAM TEMBAKAU TEROPTIMAL DI DESA ROWO KECAMATAN KANDANGAN KABUPATEN TEMANGGUNG - Setyawati, Erna; Indrayati, Ariyani (Edu Geography, 2016)
Temanggung is one of the most important tobacco centers in Indonesia. Based on the results of the agricultural census in 2013, the number of farm household tobacco plantations commodities reached 55.17% that spread over 20 districts. This tobacco production has fluctuated from year to year, caused by several factors that affect the production of tobacco, such as unpredictable weather. This study aims to measure the tobacco farmers knowledge about Pranata Mangsa; to create community-based lesson plan that is appropriate for the learning about the used of Rain Characteristic Data and Pranata Mangsa; and then to find out the farmerâs skill to determine the best period of tobacco planting after learning about the used of Rain Characteristic Data and Pranata Mangsa. The Research conducted on tobacco farmers in Rowo village. This study was designed as an experimental research, that using quantitative analysis methods such as percentage calculation and analysis of different test (t-test) to find out the difference or the same determination the best period of tobacco planting Â between the group given treatment and a group that was not given treatment. The results of t-test, showed that there were differences in determining the best period of tobacco planting Â between the group given treatment and were not given treatment. Therefore, treatment in the form of learning material and methods, affected farmers in determining the best period of tobacco planting, which means that the lesson plan is feasible in the learning activities